2020
DOI: 10.1037/xge0000721
|View full text |Cite
|
Sign up to set email alerts
|

Belief in unconscious repressed memory is widespread: A comment on Brewin, Li, Ntarantana, Unsworth, and McNeilis (2019).

Abstract: What does believing in repressed memory mean? In a recent paper in this journal, Brewin, Li, Ntarantana, Unsworth, and McNeilis (2019; Study 3) argued that when people are asked to indicate their belief in repressed memory, they actually think of deliberate memory suppression rather than unconscious repressed memory. They further argued that in contrast to belief in unconscious repressed memory, belief in deliberate memory suppression is not scientifically controversial. In this commentary, we show that they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…However, because Brewin and colleagues did not include a survey item on unconscious repression, it is unknown which endorsement rates would be detected for such a controversial statement. To remedy this omission, Otgaar et al (2019) specifically inquired about people’s belief in unconscious repression. They found high endorsement rates for belief in both conscious and unconscious repression (around 60%), implying that the belief in repressed memories is still widespread.…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…However, because Brewin and colleagues did not include a survey item on unconscious repression, it is unknown which endorsement rates would be detected for such a controversial statement. To remedy this omission, Otgaar et al (2019) specifically inquired about people’s belief in unconscious repression. They found high endorsement rates for belief in both conscious and unconscious repression (around 60%), implying that the belief in repressed memories is still widespread.…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…Brewin and colleagues argued that one explanation for this finding was that participants actually endorse a belief in conscious repression. In a recent study, we commented on Brewin et al’s research as they did not specifically ask participants about their beliefs in unconscious repression (Otgaar, Wang, Howe, et al, 2020). We corrected this shortcoming and also surveyed participants (Study 1: N = 230; Study 2: N = 79) about their belief in unconscious repression.…”
Section: Surveys On Unconscious Repressed Memorymentioning
confidence: 99%
“…We have shown that, contrary to Brewin’s assertions, many scholars continue to refer to unconscious repression. Furthermore, large percentages of people endorse this concept (e.g., Otgaar, Wang, Howe, et al, 2020). Apart from problems concerning the notion of unconscious repression, it is also important to discuss memory phenomena related to unconscious repression (i.e., memory suppression) and the memory wars (i.e., false memories).…”
Section: Memory Suppression and False Memoriesmentioning
confidence: 99%
“…The results of Chapter 4 are in line with previous studies on memory beliefs (Akhtar et al, 2018;Brewin et al, 2019;Dammeyer et al, 1997;Dodier, Melinder, Otgaar, Payouw, & Magnussen, 2019;Golding et al, 1996;Gore-Felton et al, 2000;Magnussen & Melinder, 2012;Ost et al, 2013;Otgaar, Wang et al, 2019;Patihis et al, 2014;Yapko, 1994). In general, based on the recent surveys examining memory beliefs, it can be concluded that the belief in the controversial topic of repressed memory is very much alive.…”
Section: Beliefs About Memorysupporting
confidence: 85%
“…Recent surveys suggest that some therapists continue to hold controversial beliefs about memory. Ost and colleagues (2013) Brewin et al, 2019;Otgaar, Wang et al, 2019). Still, controversial beliefs that are held firmly by clinicians (e.g., believing in repressed memories without reservation) may be problematic in a treatment setting .…”
Section: Introductionmentioning
confidence: 99%